Steel Beam Compressive Strain Sensor Using Single-Mode-Multimode-Single-Mode Fiber Structure - S. E. F. Masnan; A. Z. Zulkifli; N. M. Azmi; S. M. Akib; H. A. Razak; H. Arof; S. W. Harun (IEEE Photonics Journal, 2016)
A steel beam compressive strain sensor using single-mode-multimode-single-mode (SMS) fiber structure is demonstrated. Parallel measurements are made using an electrical resistance (ER) strain gauge along with the SMS to sense the compressive strain on the steel beam. The ER strain gauge result shows that the steel beam has an elastic limit at a compressive load of 42 kN, as predicted via calculation. On the other hand, the SMS sensor is capable to detect the elastic limit by its significant increase in the slope of the peak center wavelength from compressive strain of 0.000261–0.001986 mm/mm. Moreover, the SMS sensor exhibits compressive strain sensitivity of −1411.2 nm/(mm/mm) from the initial load until it reaches the beam elastic limit.